OPTIMISATION OF CHATGPT IN ACADEMIA – A CONCEPTUAL FRAMEWORK (CAHIERS MAGELLANES-NS, 2024)
This article explores the optimisation of ChatGPT, developed by OpenAI, in the field of academia. It proposes a conceptual framework to integrate ChatGPT into various academic functions, enhancing research, teaching, and administrative tasks. By leveraging its capabilities in natural language processing and machine learning, ChatGPT can revolutionize the academic landscape, providing unprecedented support and innovation. As ChatGPT increasingly becomes integrated into educational settings, optimizing its functionality becomes paramount for enhancing learning experiences. This paper proposes a conceptual framework for the optimization of ChatGPT in academia, focusing on key aspects such as the attitude of the instructor, institutional policies on digital usage, professional development of educator’s and educational impact.